Analysis of the Preparation of Financial Statements Based on SAK EMKM at Mas Farhan's Durian Ice Business - Athaya, Nada; Tamba, Rani Rosya; Safitri, Tsamara; Panjaitan, Gloria; Franita, Riska (Indonesian Journal Publisher, 2025)
Over time, public demand for refreshing beverages has continued to increase, driving the growth of micro, small, and medium enterprises (MSMEs) in the culinary sector. One of Mas Farhan's micro, small and medium enterprises (MSMEs), which has been operating for more than twelve years, has promising business prospects. However, this business has not yet implemented the recording and preparation of financial statements in accordance with the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM). This study aims to assist business owners in understanding and preparing financial statements in accordance with SAK EMKM, which includes a statement of financial position, income statement, and notes to financial statements. Descriptive qualitative method was used by conducting interviews and direct documentation from business people. The research shows that business owners begin to understand the importance of recording transactions in a structured manner when they receive assistance when preparing financial statements. One of the advantages of implementing SAK EMKM is that these financial statements can be a reference for business owners when they make their financial statements, allowing them to assess the performance of the business, whether it is making a profit or a loss. In addition, this study recommends continuous training to increase the awareness and ability of MSMEs actors to apply relevant and simple accounting standards.